تسجيل جديد للحبار الطائر (Lesueur, 1821) Ommastrephaes bartramii في المياه الشاطئية السورية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
ضمن دراسة تنوع وتوزع الرخويات رأسيات القدمCephalopoda في المياه البحرية السورية؛ يسجل وجود الحبار Ommastrephaes bartramiiلأول مرة محلياً، تم الحصول على ثلاثة أفراد خلال شهري آذار ونيسان من عام 2016، فردان تم جمعهما من شاطئ رأس البسيط وفرد واحد من شاطئ جبلة، على أعماق تراوحت ما بين 40-130م، أخذت القياسات المورفومترية اللازمة وقد تراوحت أطوال البرنس مابين 36,6 -50,3 سم وعرضه مابين12,1-19سم، و طول الزعنفة مابين 17,3-23,3سم، وعرض الزعنفة مابين 14,3-16سم، وطول الذراع التكاثري مابين 46,5- 73سم وتراوحت أوزان الأفراد مابين 2555,80-3954غ، كما تم تشريح العينات و وزنت الغدد الجنسية والغدد الهاضمة،حيث تراوحت أوزان الغدة الجنسية مابين 20,6-41,12غ ، أما الغدة الهاضمة فتراوح وزنها مابين86,68-102,25غ, وقد لوحظ بأن الأفراد الثلاثة التي تم الحصول عليها هي إناث.During the study of Molluscs/Cephalopods and their diversity and distributionin the Syrian marine waters; the presence of squid Ommastrephaes bartramii has recordedfor the first time locally, three individuals were collected during March and April of 2016, twoindividuals from the Ras Al-basset coast and one from Jablehcoast, at depths ranging from 40-130m, the required morphometric were done.mantle lengths has ranged from 36.6 to 50.3 cm and 12,1-19cm widethe, fin is in the size of 17,3-23,3cm,and 14,3- 16 cm wide, the proliferative arm is in the range size of 46.5 to 73 cm long. the individuals weights vary between 2555,80-3954g. Anatomy of the samples was performed also. The gonad vary between 20,6-41,12g, and the digestive gland weight ranged between 86,68-102,25g, has been observed all of the three individual were females..